Magnetic Control of Tokamak Plasmas - Ariola, Marco; Pironti, Alfredo; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2008)
The problem of confining a plasma, with sufficiently high density and temperature, is of crucial importance if nuclear fusion is to be made usable as a form of power generation. Tokamaks – devices with a toroidal geometry – are among the most popular candidates by which such confinement can be achieved. A tokamak separates a plasma from its surroundings by means of a magnetic field generated by several coils distributed around the plasma. The main topic of Magnetic Control of Tokamak Plasmas is the design of feedback control systems guaranteeing the stability of plasma equilibrium inside a tokamak and the regulation of the plasma position and shape during plasma pulses. Modelling and control details are presented, allowing the non-expert to understand the control problem. Starting from equations of magneto-hydro-dynamics, all the steps needed for the derivation of plasma state-space models are enumerated. The basics of electromagnetics are frequently recalled. The control problem is then described beginning with control of current and position – vertical and radial – and progressing to the more challenging shape control. The solutions proposed vary from simple PIDs to more sophisticated MIMO controllers. Wherever possible, the various topics are rounded out with results obtained through the authors’ contributions to experiments with actual tokamaks. Mathematical details which are outside the normal province of control engineers are presented in an appendix for the interested reader. The ideas formulated in this monograph will be of great practical help to control engineers, academic researchers and graduate students working directly with problems related to the control of nuclear fusion. They will also stimulate control researchers interested more generally in the advanced applications of the discipline.
Plasma Modelling -- Plasma Modelling for Magnetic Control -- The Plasma Boundary and its Identification -- Plasma Control -- Plasma Magnetic Control Problem -- Plasma Position and Current Control at FTU -- Plasma Vertical Stabilization -- Plasma Shape Control for ITER -- Plasma Shape Control at TCV -- Plasma Shape Control at JET.
Keywords: Nuclear energy; Control engineering; Nuclear fusion; Atoms; Physics; Energy systems; Nuclear Energy; Control and Systems Theory; Nuclear Energy; Nuclear Fusion; Atomic, Molecular, Optical and Plasma Physics; Energy Systems